2012
DOI: 10.1021/am201722x
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Stability at High Temperatures for Birefringence in PAZO/PAH Layer-by-Layer Films

Abstract: Optical memories with long-term stability at high temperatures have long been pursued in azopolymers with photoinduced birefringence. In this study, we show that the residual birefringence in layer-by-layer (LbL) films made with poly[1-[4-(3-carboxy-4 hydroxyphenylazo)benzene sulfonamido]-1,2-ethanediyl, sodium salt] (PAZO) alternated with poly(allylamine hydrochloride) (PAH) can be tuned by varying the extent of electrostatic interactions with film fabrication at different pHs for PAH. The dynamics of both wr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 57 publications
2
40
0
Order By: Relevance
“…The surface roughness can result from gas evolution during deposition, related to the electrochemical decomposition of water. 29,35 The spectrum of the deposited PAZO is similar to that of the protonated form of PAZO, prepared in acidic conditions. 5E and F).…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…The surface roughness can result from gas evolution during deposition, related to the electrochemical decomposition of water. 29,35 The spectrum of the deposited PAZO is similar to that of the protonated form of PAZO, prepared in acidic conditions. 5E and F).…”
Section: Resultsmentioning
confidence: 78%
“…23 The analysis of deposition yield data at different deposition durations at PAZO concentrations of 1 g L À1 indicated that relatively high deposition yield can be achieved (Fig. 35 The adsorptions at 1396 and 1481 cm À1 were related to aromatic C-C/C]C vibrations. The deposition yield data presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been shown that the residual birefringence attained in LbL films of poly(allylamine hydrochloride) (PAH) alternated with poly[1-[4-(3-carboxy-4 hydroxyphenylazo)benzene sulfonamido]-1,2-ethanediyl, sodium salt] (PAZO) can be tuned by controlling the extent of electrostatic interactions during film fabrication. 19 In addition, it has been demonstrated that the reduction of electrostatic interactions leads to orientation of PAZO chromophores via cooperative aggregation, where the presence of polyelectrolyte counterions hinder relaxation. This result is relevant for the production of optical storage devices with long-term stability at high temperatures and, also, indicates that the growth of these films should be better characterized from of point view of adsorbed molecules and surface morphology.…”
mentioning
confidence: 99%
“…Layer-by-layer (LbL) adsorption of oppositely charged polyelectrolytes onto solid substrates has shown to be a versatile technique for the development of polyelectrolyte multilayer (PEM) films, where not only thickness and composition can be controlled precisely, but also their properties may be tuned synergistically with a combination of distinct materials in the same film [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%